Chronic pain and delinquency partially explain the effect of the DRD4 gene polymorphism on adult substance use. (4th March 2022) - Yang, James J.; Wang, Zhi; Trucco, Elisa M.; Buu, Anne; Lin, Hsien-Chang
ABSTRACT: Background : The dopamine receptor D4 [ DRD4 ] has been reported to be associated with substance use. Yet, the roles that health conditions and behaviors may play in such association are understudied. Objective : This longitudinal study investigated the potential mediation effects of chronic pain and delinquency in adolescence on the association between the DRD4 2-repeat allele and substance use in adulthood. Sex, witnessing violence, and experiencing violence were also examined as potential moderators for the mediation pathways. Methods : We used the restricted and candidate gene data from the National Longitudinal Study of Adolescent to Adult Health (Waves I–IV) to conduct secondary analysis ( N = 8, 671; 47% male). A two-step approach was adopted to examine the mediation effects regarding four substance use outcomes in adulthood: number of lifetime alcohol use disorder symptoms, lifetime regular smoker status, past-month smoking, and lifetime "pain killer" misuse. The moderation effects were investigated using stratification and permutation. Results : The DRD4 2-repeat allele was associated with all adulthood substance use outcomes through adolescent chronic pain and delinquency (AORs/IRR range 1.08–3.78; all p s<0.01). The association between delinquency and smoking was higher among females. The association between delinquency and substance use was lower among the participants who witnessed violence in adolescence. Conclusions : This study identified modifiable mediators underlying the association between the DRD4 2-repeat allele and substance use behaviors, concluding that chronic pain and delinquency partially explain the effect of the DRD4 gene polymorphism on adult substance use.